100TH ANNIVERSARY OF THE BIRTH OF V L GINZBURG. REVIEWS OF TOPICAL PROBLEMS : Quantum measurements in gravitational-wave detectors. (28th December 2016) - Khalili, F Ya
Abstract: The sensitivity of contemporary gravitational-wave detectors is so high that to a large extent it is limited by quantum fluctuations of light in them. Methods to suppress or evade these fluctuations are actively being developed, and the simplest of them, the injection of squeezed light, has already found application in the GEO600 detector. The aim of this review is first to acquaint the reader with the quantum mechanical limitations on the sensitivity of optomechanical devices in general and laser gravitational-wave detectors in particular and, second, to outline the methods for overcoming these limitations that are considered the most promising for implementation in current and planned detectors.